Preferential attention towards the eye‐region amongst individuals with insomnia. (14th September 2016) - Akram, Umair; Ellis, Jason G.; Myachykov, Andriy; Barclay, Nicola L.
Summary: People with insomnia often perceive their own facial appearance as more tired compared with the appearance of others. Evidence also highlights the eye‐region in projecting tiredness cues to perceivers, and tiredness judgements often rely on preferential attention towards this region. Using a novel eye‐tracking paradigm, this study examined: (i) whether individuals with insomnia display preferential attention towards the eye‐region, relative to nose and mouth regions, whilst observing faces compared with normal‐sleepers; and (ii) whether an attentional bias towards the eye‐region amongst individuals with insomnia is self‐specific or general in nature. Twenty individuals with DSM‐5 Insomnia Disorder and 20 normal‐sleepers viewed 48 neutral facial photographs (24 of themselves, 24 of other people) for periods of 4000 ms. Eye movements were recorded using eye‐tracking, and first fixation onset, first fixation duration and total gaze duration were examined for three interest‐regions (eyes, nose, mouth). Significant group × interest‐region interactions indicated that, regardless of the face presented, participants with insomnia were quicker to attend to, and spent more time observing, the eye‐region relative to the nose and mouth regions compared with normal‐sleepers. However, no group × face × interest‐region interactions were established. Thus, whilst individuals with insomnia displayed preferential attention towards the eye‐region in general, this effect was not accentuated during self‐perception. Insomnia appears to be characterized by a general, rather than self‐specific, attentional bias towards the eye‐region. These findings contribute to our understanding of face perception in insomnia, and provide tentative support for cognitive models of insomnia demonstrating that individuals with insomnia monitor faces in general, with a specific focus around the eye‐region, for cues associated with tiredness.